Evolution of human language: duetting as part of prosociality and cognition - Kaplan, Gisela (Frontiers in Ecology and Evolution, 2023)
The evolution of human language is a topic that has received undiminished attention. Numerous hypotheses for the origin of human language have been proposed, including gestural communication found specifically among apes. This study advances the hypothesis that human evolution, including human language development, is three-pronged: prosocial, cognitive, and collaborative. Duetting and turn-taking in primates are used as pivotal examples of how bonding leads to joint action and collaboration. It points out that such vocal behavior itself may be a crucial precursor of language evolution in the sense that it is explicitly focused on a conspecific. Some current hypotheses have acknowledged duetting as an important perceptual and behavioral example of synchronicity. Some forms of synchronized behavior, as found in duetting, synchronized dance, or even shared song, were perhaps crucial evolutionary steps preceding the evolution of human language. Duetting signifies more than that, however, because it is an observable and significant cognitive investment that signals attention toward a partner. This study also advances the hypothesis that affect and cognition would have needed to precede any form of duetting or signs of affiliation such as grooming. Hence, this study, asking what duetting in primates signifies in evolutionary terms, takes a multidisciplinary and multimodal approach to suggest important affective and cognitive steps in the evolution of human language and speech, the chief of which is prosociality. Prosociality, as an attitude and awareness of another, be this as a friend or partner for whom one can do favors or whom one can help, is a model for collaboration and cooperation, and also increased cognition.